2021
DOI: 10.31223/x5tw4b
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Will it float? Rising and settling velocities of common macroplastic foils

Abstract: Plastic accumulates in the environment because of insufficient waste handling and the materials' high durability. Better understanding of plastic behaviour in the aquatic environment is needed to estimate transport and accumulation, which can be used for monitoring strategies, prevention measures, and plastic clean-up activities. Plastic transport models benefit from accurate description of particle characteristics, such as rising and settling velocities. For macroplastics, these are however still scarce. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Other studies reported a rather uniform distributed of plastics over the water column Broere et al., 2021, Haberstroh et al., 2021, or a clear peak concentration at the surface (Haberstroh et al., 2021). The few available studies demonstrate that the vertical distribution is far from trivial, and may depend on flow conditions, and plastic item characteristics (e.g., size, shape, effective buoyancy) (Kuizenga et al., 2022). The main challenge remains data collection below the surface, as it involves heavy equipment such as nets, boats, and cranes (Blondel & Buschman, 2022; Liedermann et al., 2018), or relies on novel technology that is still under development, including sonar (Broere et al., 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Other studies reported a rather uniform distributed of plastics over the water column Broere et al., 2021, Haberstroh et al., 2021, or a clear peak concentration at the surface (Haberstroh et al., 2021). The few available studies demonstrate that the vertical distribution is far from trivial, and may depend on flow conditions, and plastic item characteristics (e.g., size, shape, effective buoyancy) (Kuizenga et al., 2022). The main challenge remains data collection below the surface, as it involves heavy equipment such as nets, boats, and cranes (Blondel & Buschman, 2022; Liedermann et al., 2018), or relies on novel technology that is still under development, including sonar (Broere et al., 2021).…”
Section: Resultsmentioning
confidence: 99%